Endometrial MicroRNA Signature during the Window of Implantation Changed in Patients with Repeated Implantation Failure - Shi, Cheng (Chin Med J (Engl), 2017)
BACKGROUND: At present, a diagnostic tool with high specificity for impaired endometrial receptivity, which may lead to implantation failure, remains to be developed. We aimed to assess the different endometrial microRNA (miRNA) signatures for impaired endometrial receptivity by microarray analysis. METHODS: A total of 12 repeated implantation failure (RIF) patients and 10 infertile patients, who conceived and delivered after one embryo transfer attempt, were recruited as RIF and control groups, respectively. Endometrial specimens from the window of implantation (WOI) were collected from these two groups. MiRNA microarray was conducted on seven and five samples from the RIF and control groups, respectively. Comparative, functional, and network analyses were performed for the microarray results. Quantitative real-time polymerase chain reaction (PCR) was performed on other samples to validate the expression of specific miRNAs. RESULTS: Compared with those in the control group, the expression levels of 105 miRNAs in the RIF group were found to be significantly up- or down-regulated (at least 2-fold) by microarray analysis. The most relevant miRNA functional sets of these dysregulated miRNAs were miR-30 family, human embryonic stem cell regulation, epithelial-mesenchymal transition, and miRNA tumor suppressors by tool for annotations of microRNA analysis. Network regulatory analysis found 176 miRNA-mRNA interactions, and the top 3 core miRNAs were has-miR-4668-5p, has-miR-429, and has-miR-5088. Expression levels of the 18 selected miRNAs in new samples by real-time PCR were found to be regulated with the same trend, as the result of microarray analysis. CONCLUSIONS: There is a significant different expression of certain miRNAs in the WOI endometrium for RIF patients. These miRNAs may contribute to impaired endometrial receptivity.